The concept of personal data protection culture from European Union documents: a “Brussels effect” in Latin America? - Veronese, Alexandre; Silveira, Alessandra; Lemos Igreja, Rebecca; Lopes Espiñeira Lemos, Amanda Nunes; Guimarães Moraes, Thiago (UNIO – EU Law Journal, 2023)
This article aims to analyse, based on documentary sources and data collected through extensive field research, the potential cultural influence of EU (European Union) standards for protecting personal data in Latin American countries, which have data protection authorities and specific laws on the subject. The text has two sections, with an introduction and a conclusion. The introduction presents the subject, indicating the sources that lead up to the text analysis and conclusions. In the first section, the article deals with the EU’s data protection model from its fundamentalist legal perspective. The second section deals with constructing the personal data protection culture concept and how extensive EU documents research can help infer it. The conclusion indicates that the EU’s data protection perspective – as a fundamental right and public policy – can potentially influence several Latin American countries. Also, it concludes that there is an evident difficulty in culturally measuring greater or lesser effectiveness in protecting personal data based on the documents. Despite this dilemma, the EU documentation points to some qualitative suggestions that deserve to be incorporated into the analysis of cultures of personal data protection, focusing on Latin American countries.